Experimental Study on the Smoke Temperature Decrease near Natural Vents Induced by Air Entrainment in a Tunnel Fire - Yu, Hai; Yang, Yunhao; Yin, Jiyao; Deng, Peng; Sun, Yanlong; Zhou, Lin; Liu, Zhenguo (Advances in Civil Engineering, 2023)
Previous studies have shown that there is a large difference in the temperature of smoke in the upstream and downstream of a vertical shaft, but no quantitative study on the subject has been conducted. In this paper, a model experimental test was conducted to study the effect of a natural vertical shaft on the distribution of smoke temperature in tunnel fires. A laser sheet was used as an assisting tool to show the smoke flow field. A series of tests were conducted with shaft heights varying from 0.2 m to 1.2 m and a heat release rate (HRR) of 9 kW, 17 kW, 29 kW, and 65 kW. The entrainment phenomenon around the vertical shaft was analyzed, and the results showed that the amount of fresh air entrainment is the main reason for the temperature decrease in upstream and downstream smoke temperatures. Based on the experimental results, an empirical model for predicting the amount of fresh air entrainment and a prediction model of the downstream smoke temperature were proposed, and the predicted values are in good agreement with the experimental values.